A case study of the drivers and barriers of implementation of the Baby Friendly Hospital Initiative (BFHI) within a rural sub-district in South Africa - Brittin, Katherine (Department of Public Health and Family Medicine, 2015)
Exclusive breastfeeding is recognised as a key child survival strategy in the South African context and the Baby Friendly Hospital Initiative (BFHI) accreditation for maternity facilities is recommended by the National Department of Health (NDOH) as crucial to improving the standards of care required for optimal support for mothers to successfully breastfeed. The Cape Winelands District in the Western Cape is a region that needs to improve the accreditation rate for its facilities. Key informant interviews were conducted within rural maternity services in the Breede Valley Sub-District. Interviews identified the barriers and enablers related to the health system building block 'information'. An additional goal was to examine communication and how information was disseminated throughout all levels of the health system to achieve the aim of successful policy implementation of the BFHI. Findings demonstrated that personal experiences of healthcare personnel may impact on the information offered to mothers. In addition, the operational manager of a facility possessed significant influence to ensure a policy was implemented and adhered to. Recommendations include advocating for education promoting breastfeeding in all healthcare programmes especially during the antenatal period by providing consistent, non-conflicting messages. Management should provide vision and strong leadership around implementation of the BFHI policy and ensure effective communication strategies around significant changes in the policy. Implementing BFHI is a complex context specific activity and to ensure optimal implementation of "Step three" (inform pregnant women of the benefits and management of breastfeeding) it is necessary to examine this particular area by using the recommendations as a framework in order to probe further.